2018
DOI: 10.1093/nutrit/nuy031
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic and probiotic treatment of nonalcoholic fatty liver disease: a systematic review and meta-analysis

Abstract: This meta-analysis supports the potential use of microbial therapies in the treatment of NAFLD and sheds light on their potential mode of action. Further research into these treatments should consider the limitations of biomarkers currently used for the diagnosis and progression of NAFLD, in addition to the inherent challenges of personalized microbial-based therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 68 publications
4
80
1
4
Order By: Relevance
“…The authors also noted that BMI, glucose, and low‐density lipoprotein did not improve after probiotic treatment . Recently, several meta‐analyses have evaluated the effects of probiotics on liver histology . The authors did report the favorite effects of probiotic in NASH.…”
Section: Anti‐oxidants and Cytoprotective Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also noted that BMI, glucose, and low‐density lipoprotein did not improve after probiotic treatment . Recently, several meta‐analyses have evaluated the effects of probiotics on liver histology . The authors did report the favorite effects of probiotic in NASH.…”
Section: Anti‐oxidants and Cytoprotective Therapiesmentioning
confidence: 99%
“…At present, however, there is no uniformity in the outcomes assessed. Moreover, it remains to be elucidated whether the type of microbial therapy, the dose used of treatment, and the duration of therapy affect outcomes or not …”
Section: Anti‐oxidants and Cytoprotective Therapiesmentioning
confidence: 99%
“…Although far less studied in the context of liver disease than probiotics, recent developments in prebiotic research, coupled with a relatively benign regulatory landscape, may soon see precisely tailored prebiotic molecules directed at the management of certain liver diseases. Early data are encouraging …”
Section: Interventions That Modulate the Gut Microbiomementioning
confidence: 99%
“…The World Health Organization defines probiotics as "live microorganisms which when administered in adequate amounts confer a health benefit on the host" [1]. The popularity of the beneficial e↵ects of microorganisms has become progressively widespread over the decades, alongside our increasing awareness of the e↵ects that bacteria can exert on health and disease such as inflammatory bowel disease (IBD) and non-alcoholic fatty liver disease (NAFLD) [2,3]. By now, consumption of probiotics in an attempt to maintain health and prevent, ameliorate, or resolve disease has become routine.…”
mentioning
confidence: 99%
“…Many studies have investigated the e↵ects of probiotics, but the majority of those studies that have causally linked probiotics to positive outcomes have been carried out in animal models [5,6]. Several meta-analyses of studies performed in humans have indicated promising results, particularly in the context of ameliorating the symptoms of those people already su↵ering from diseases like IBD and NAFLD [2,3]. However, these human studies tend to be less conclusive and in some cases yield contradictory results [7].…”
mentioning
confidence: 99%